HUBUNGAN KONTROL DIRI DENGAN PERILAKU MENYONTEK SISWA - Yovita, Desi; Ahmad, Riska (Universitas Negeri Padang, 2018)
Cheating behavior is fraud committed by students when doing school assignments, homework and examinations. This study aims to: (1) describe the self-control of students, (2) describe the behavior of cheating students, and (3) test the significance of the relationship of self-control to cheating behavior on students. This study uses quantitative methods with descriptive correlational types. The research subjects were 267 students from SMKN 1 Batusangkar. The instrument used is a self-control questionnaire and cheating behavior questionnaire that has been tested for validity and reliability. Data were analyzed by descriptive statistical techniques and Pearson Product Moment techniques with the help of SPSS for Windows 20. Based on the results of the study showed that: (1) self control in students was in the sufficient category with a percentage of 62.47%, (2) student cheating behavior was in the medium category with a percentage of 77.08%, (3) and there is a significant negative relationship between self-control and cheating behavior on students with a correlation coefficient of -0.336 and a significance level of 0.000.